Modeling and Prediction Analysis of Magnetic Field in DC Yard of VSC-HVDC Station under Short Circuit Condition - Meng BAO; Hong SHEN; Jialiang LI; Yan SHI; Lei QI; Qian WANG (Zhongguo dianli)
For the voltage source converter based high voltage direct current (VSC-HVDC) station equipped with hybrid DC breakers, the DC circuit breaker has fast speed for breaking fault current and short time for internal commutation. The electromagnetic influence of magnetic field caused by fault current on secondary equipment in DC field is not clear. A multi-path magnetic field calculation model of hybrid DC circuit breaker and a magnetic field calculation model of smoothing reactor and DC bus are established to predict the magnetic field around the secondary equipment in the DC field of Dinghai Converter Station and Zhangbei Converter Station with bipolar short circuit fault at the DC side, and the distribution characteristics of magnetic field in the DC yard is obtained. The calculation results show that the peak value of magnetic field intensity around the existing secondary equipment in the DC field of Dinghai Converter Station and Zhangbei Converter Station can reach 883 A/m and 362 A/m respectively; the peak value of magnetic field intensity occurs at the time when the fault current reaches its peak value or the DC breaker has the second commutation; the magnetic field intensity is higher near the smoothing reactor and at the location where there are many buses in the DC yard. The calculation results can provide a reference for the evaluation of secondary equipment immunity and the layout of electrical equipment.